Motive for Divorce among The Elderly in Padang City - Fachrina Fachrina; Nini Anggraini (Mahesa Research Center, 2023)
This article aims to describe the motives for divorce among the elderly (elderly). The problem is focused on the married life of elderly couples, what are the because motives and in order to motive the elderly to divorce at a relatively long age of marriage. To approach this problem, a theoretical reference from Alfred Shuzt is used. Data was collected through free interviews with elderly people who were at least 60 years old, had been married for more than 25 years and had children and were divorced. Observations were also made to observe the life and activities of the elderly. The data obtained was analyzed qualitatively. This study concludes that the married life of the elderly, which initially runs harmoniously as they get older, tend to experience quarrels which cause disharmony in the relationship with their partner and finally decide to take divorce steps. The motive for the elderly deciding to divorce is dominated by sexual problems. Another reason is infidelity and polygamy by husbands, husbands leave the house and wives are busy taking care of their children and grandchildren. The in order to motive is to want to get out of marital problems, live quietly in old age and free oneself from obligations as a wife. However, it was found that this motive did not stand alone, but was an accumulation of various things.